Analysis of Outsourcing System and Work Motivation on Employee Performance - Neng Eti Setiawati (Journal of Business and Behavioural Entrepreneurship, 2021)
Background - Currently, many companies are implementing outsourcing systems for their company's HR management. Outsourcing is a company that uses human resources from other parties (external) to carry out work activities that are usually handled by internal staff and resources. The problem that exists is because the outsourcing system affects the performance of employees at a food ingredients factory in Cilegon, where there are still high complaints from clients regarding the decline in the performance of forklift operator employees placed in their company. This shows the inaccuracy at work leads to a lack of employee motivation. Employee motivation problems can be the cause of low employee performance in a company. Purpose - The objectives of this study are (1) to determine the effect of the outsourcing system on employee performance and (2) to see the effect of work motivation on employee performance. Originality/Value - This study tested 2 hypotheses with data sources originating from respondents of outsourcing employees of PT. AMP, a division of forklift operators at the Cilegon grocery factory, analyzed the influence of the outsourcing system and work motivation on employee performance in the company. Research Limitations - information, primary and secondary data in this study were only obtained from PT. AMP Design/methodology/approach - The population and sample of this study were all outsourced employees of PT. The AMP division of forklift operators placed 30 people in a food ingredients factory in Cilegon. This study uses a quantitative approach method. The data collection technique used primary data in the form of a questionnaire. The data analysis technique of this research used the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. Findings - Based on the results of the direct influence hypothesis research, it is known that the outsourcing system has a positive and significant effect on employee performance. And motivation has no significant effect on employee performance